Implementasi Mutaba’ah Amalan Harian Santri sebagai Strategi Penguatan Karakter di Madrasah Diniyah Darunnajah Al-Ma’sudiyah - Siti Amanah; Izzatun Nafisah; Adinda Nashwa Meutya Anam; Novena Ade Fredyarini Soedjiwo (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to evaluate the effectiveness of the Daily Practice Monitoring (Mutaba’ah) program in strengthening religious character and discipline at Madrasah Diniyah Darunnajah Al-Ma’sudiyah, Denpasar. The study employed a Participatory Action Research (PAR) approach involving teachers, administrators, and students in the stages of problem identification, action planning, implementation, and reflection. The program was conducted over two days in response to declining student discipline and learning focus caused by excessive gadget use and limited reflective practices in daily worship. Qualitative data were collected through observation, interviews, and documentation and analyzed using data reduction, display, and verification. The findings show a significant improvement in students’ discipline, responsibility, and consistency in performing daily religious practices. Attendance at congregational prayers increased by 90%, accompanied by improved learning focus and reflective awareness. These results indicate that Daily Practice Monitoring is an effective participatory strategy for character education in Islamic schools to address moral and disciplinary challenges in the digital era.